Evaluation of the role of unconventional prefoldin RPB5 interactor (URI1) in hepatitis B virus infection - Karolína Štaflová; Aleš Zábranský; Iva Pichová (Virology Journal)
Abstract Hepatitis B virus (HBV) infection can cause liver disease and lead to hepatocellular carcinoma (HCC). To better understand the factors involved in viral infection and pathogenesis and to develop novel therapies, it is crucial to investigate virus–host interactions. HBV infection has been shown to increase the expression of the unconventional prefoldin RPB5 interactor (URI1), a cellular protein that promotes liver tumorigenesis and HCC metastasis. Our study investigated the role of URI1 in HBV infection in vitro. Although previous reports have suggested that URI1 may act as an HBV restriction factor, our results showed that URI1 silencing or overexpression did not affect HBV replication in HepG2-NTCP cells. In primary human hepatocytes, URI1 knockdown modestly reduced HBV markers but did not significantly alter acute infection. Supporting the premise that URI1 is a promising therapeutic target for HCC, our findings show that URI1 knockdown does not enhance HBV infection in an acute infection model. This suggests that URI1 may be a viable therapeutic target for patients with HBV-associated HCC without increasing HBV-related complications.